Síntesis y evaluación de recubrimientos base fluoruro empleando fuentes alternativas al HF sobre la aleación Elektron 21 para la fabricación de implantes ortopédicos biodegradables (2015)
Magnesium has been postulated as an excellent candidate for fabrication of biodegradable implants because of its degradability, biocompatibility and excellent mechanical properties comparable to bone’s those. Nevertheless, its high corrosion rate represents a great disadvantage, allowing the approach of modifying its electrochemical behaviour by the design of biodegradable coatings. In this regard, the most common synthesis route employed is chemical conversion in HF (up to 48%v) to produce biodegradable magnesium fluoride coatings. However, it is well known that HF is an extremely hazardous acid. Thus, one of the main targets is to find other alternative routes to avoid its use or, at least, to reduce its concentration. In the present investigation HF(4%v) -NaF and H3PO4-NaF solutions were evaluated as alternatives of the HF route to produce biodegradable coatings on the Elektron 21 magnesium alloy. Characterization of the conversion coatings was carried out by scanning electron microscopy and X-ray diffraction, whereas their corrosion resistance was evaluated by electrochemical and gravimetric measurements in Hank solution at 37°C. The results showed that the addition of NaF to the reactive solution promotes the formation of a double layer of MgF2-x(OH)x/NaMgF3. The presence of the NaMgF3 prevents the pitting corrosion attack of the coating/alloy system and leads a more uniform degradation mechanism. Particularly, the coating synthesized using H3PO4 1.6%v-NaF 0.5M solution exhibited an excellent electrochemical behaviour, better that obtained employing HF solutions so that, it might be proposed as excellent candidate to replace the HF in the synthesis of biodegradable coatings.